2000
DOI: 10.4049/jimmunol.164.11.6015
|View full text |Cite
|
Sign up to set email alerts
|

Simian Immunodeficiency Virus (SIV)-Specific CTL Are Present in Large Numbers in Livers of SIV-Infected Rhesus Monkeys

Abstract: The immunopathogenesis of AIDS-associated hepatitis was explored in the SIV/rhesus monkey model. The livers of SIV-infected monkeys showed a mild hepatitis, with a predominantly CD8+ T lymphocyte infiltration in the periportal fields and sinusoids. These liver-associated CD8+ T cells were comprised of a high percentage of SIV-specific CTL as defined by MHC class I/Gag peptide tetramer binding and Gag peptide epitope-specific lytic activity. There was insufficient viral replication in these livers to account fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…Consistent with our previous findings in studies of tetramer-binding CD8 ϩ T lymphocytes in the peripheral blood and lymphatic tissues of chronically SIVmacinfected rhesus monkeys, 8,9,[16][17][18] we observed that the tetramerbinding CD8 ϩ IELs or LPLs from the ileum and jejunum had a phenotypic appearance consistent with their being activated. An example of a phenotypic analysis of tetramer-binding CD8 ϩ jejunal LPLs is shown in Figure 2.…”
Section: Tetramer-binding Gi Cd8 ؉ T Lymphocytes Have An Activated Phsupporting
confidence: 81%
“…Consistent with our previous findings in studies of tetramer-binding CD8 ϩ T lymphocytes in the peripheral blood and lymphatic tissues of chronically SIVmacinfected rhesus monkeys, 8,9,[16][17][18] we observed that the tetramerbinding CD8 ϩ IELs or LPLs from the ileum and jejunum had a phenotypic appearance consistent with their being activated. An example of a phenotypic analysis of tetramer-binding CD8 ϩ jejunal LPLs is shown in Figure 2.…”
Section: Tetramer-binding Gi Cd8 ؉ T Lymphocytes Have An Activated Phsupporting
confidence: 81%
“…The increased expression of adhesion molecules and chemokine receptors on HIV-specific CD8 ϩ T cells in CSF during HIV infection also suggests that the trafficking of antigen-specific T cells to the brain may be due to a combination of the systemic activation of T cells and response to intrathecal inflammation (69). Our finding may not be unique to the brain, since in SIV-infected macaques high frequencies of virus-specific T cells have been demonstrated in the gastrointestinal tract, urogenital tissue, spleen, bone marrow, and liver compared to what is seen for peripheral blood (32,46,68,73). Recent data from a rodent model suggest that the expression of viral antigens in the brain may upregulate endothelial cell major histocompatibility complex class I expression, which in turn favors CD8 ϩ T-cell migration into the brain (27).…”
Section: Discussionmentioning
confidence: 63%
“…Although several studies report a failure of HIV-specific CTL to colocalize with HIV-infected cells (35,41,47,48,55), others have demonstrated equivalent or higher levels of ex vivo functionally active CTL in mucosal and lymphoid tissue compared to peripheral blood (5,32). Except in the rare cases of long-term nonprogressors who immunologically control HIV-1 and demonstrate increased levels of perforin expression and proliferative capacity of their HIV-specific CTL (40), additional analyses of markers of in vivo functional activity, such as in situ granzyme B expression and apoptosis, have revealed low levels of actual cytolysis at the interface between virus-specific CTL and HIV-infected cells (6,14).…”
Section: Vol 78 2004mentioning
confidence: 99%
“…In SIV infection, the total numbers and proliferative capacity of virus-specific CTL are decreased in lymphoid tissue compared to blood (35,41). Additionally, SIV-infected monkeys have demonstrated a significant accumulation of virus-specific CTL in the liver without a concomitant focus of viral replication (55). In primary, untreated HIV-1 infection, a significant number of HIV-specific CTL rapidly disappear while viral load persists at high levels (48).…”
mentioning
confidence: 99%